PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN TERHADAP INDEKS PEMBANGUNAN MANUSIA DI KABUPATEN ACEH SELATAN - Hanafi Hanafi; T. Zulham (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
Abstract This study aims to analyze the relationship between government spending on education in the human development index in South Aceh District. The type of data used is secondary data obtained from BPS. The data used is the annual time series data from 2008 - 2017. The data analysis method used is a simple linear regression method. The results showed that the government expenditure on the education sector had a positive and significant effect on the human development index in South Aceh District. The result of processing determinant (R-squared) coefficient is 0.854359. This illustrates that the independent variable affects the dependent variable by 85.43 percent, while 14.57 percent is explained by other variables not included in the model or explained in error term (ε). Partial value of p value t is 0.0001 where 0.05 so that it accepts H1 or which means that the independent variable has a partial effect in the model on the dependent variable. The government in the future is expected to be able to manage education spending effectively, so that it can push the HDI level higher. Based on these findings, it is expected that further research is suggested to examine health sector expenditures and GRDP against the HDIKeywords : Education Sector Government Expenditures, Human Development Index, HDI.